Effects of land applications waste water of crude palm oil factory on some nutrient available in soil and nutrient content in palm oil - Irwan Sukri Banuwa; Mamat Anwar Pulung (UNIVERSITY OF LAMPUNG, 2008)
An experiment was aimed to study effect of waste water of crude palm oil (CPO) factory on some nutrient available in soil and nutrient content in palm oil. The experiment was conducted using a completely randomized block design with six levels of waste water treatments (0, 250, 500, 750, 1.000, and 1.250 L tree-1 palm oil) in three replications. The result showed that the level 750 L tree-1 of waste water treatment have significant effects on increased of nutrient available in soil (N, P, K, Ca, and Mg) including soil pH, but not significant with level 1000 and 1250 L tree-1 except P. On the other hand, nutrient content in palm oil (N, P, and K) were not significantly influenced by waste water treatments.